C-ANCA vasculitis after initiation of denosumab. Issue 3 (1st March 2019) - Sanchez, Alexandra; Lozier, Matthew; Adkinson, Brian Cody; Ilaiwy, Amro
Abstract : Denosumab is a fully human antibody to receptor activator of nuclear factor kappa-B ligand (RANKL), and it is administered every 6 months in women with postmenopausal osteoporosis (PMO) at high risk for fracture. Adverse effects of denosumab include musculoskeletal pain, hypercholesterolaemia, symptomatic hypocalcaemia, osteonecrosis of the jaw and cutaneous events such as angioedema, cellulitis and pustular dermatitis. While the possibility of vasculitis was mentioned in the product Monograph as well as in the WHO Newsletter, this is the first case, to our knowledge, of cytoplasmic-ANCA (c-ANCA) associated vasculitis officially published in the literature. 1 2 The pathogenic mechanisms behind drug-induced vasculitis remain to be defined and appear to be multifactorial. Once suspicion for drug-induced vasculitis arises, the offending agent should be discontinued and immunosuppressive therapy should be initiated according to the severity of organ involvement to inhibit progression to severe, irreversible disease. As new medications continue to be developed, the number of agents causing drug-induced vasculitis is expected to increase.